Odontogenic sinusitis and brain abscesses due to Staphylococcus xylosus: First case report - Salazar-Zuloeta, Jaime Ysrael; Tello-Vera, Stalin; Becerra-Gutiérrez, Lizzie Karen (Acta Biomedica Atenei Parmensis, 2025)
Background and objective: Odontogenic infections are potentially fatal infectious processes caused by caries, periodontal disease, or dental procedures. This study aims to identify CNS complications caused by periodontal disease or dental procedures. Methods: The present study presents the case of a 40-year-old diabetic patient on irregular oral hypoglycemic treatment who, 7 days after the extraction of the upper left first molar, began to present pain in the area of the dental procedure, erythema, edema of the hemiface, left proptosis and frontal headache, but remained afebrile at all times. He was admitted to the emergency department of the Almanzor Aguinaga Asenjo Hospital in Chiclayo, Peru, where different examinations and treatments were performed. Results: The patient presented tonic-clonic seizures; cranial tomography revealed sinus collections at maxillary, frontal, and left ethmoidal levels. In addition, there were brain abscesses in the frontal region of the same side. He received ceftriaxone associated with metronidazole, both intravenously in addition to surgical drainage of the abscesses. Staphylococcus xylosus was identified in samples obtained from the left maxillary sinusotomy; medical treatment was successful, but the patient was left with chronic osteomyelitis in the walls of the paranasal sinuses and orbit. Conclusions: This case highlights the importance of preventing or detecting suppurative complications in the central nervous system in diabetics or other immunosuppressed patients caused by periodontal disease or dental procedures.